A STUDY ON THE ABILITY OF THE THIRD SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP OF RIAU UNIVERSITY IN COMPREHENDING THE ERNEST HEMINGWAY “SOLDIER HOME” SHORT STORY - Wiwiek Angraini; Masyhur '; Syafri K (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was aimed to find out the ability of the third semester students of English study program of FKIP of Riau University in comprehending the Ernest Hemingway “soldier home” short story. The researcher used cluster random sampling technique to determine the sample. The samples were 35 students. The study was used to find out the ability in five elements of fictions such as subject, events, setting, character and moral value. Multiple choice was used to gain the data with the number of tests is 20 questions. The result of the study revealed that the total mean score was 63.71 which indicated students were in good level of ability. The highest score with the mean score 77 was in the subject, it is in good level. Whereas, the lowest score with the mean score 34.28 was in the moral value, it is in poor level of ability.Keywords: Students’ ability, Literature, Short Story